1984
DOI: 10.1111/j.1545-5300.1984.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Rituals

Abstract: Family rituals, consisting of celebrations, traditions, and patterned family interactions, are defined and illustrated in this paper. The power of ritual practice in families is explained by three underlying processes — transformation, communication, and stabilization — concepts whose roots lie in anthropology and ethology. We propose that all families struggle with finding a suitable role for rituals in their collective lives but their actual achievement varies greatly. Commitment to ritual and adaptability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
197
0
10

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(210 citation statements)
references
References 4 publications
3
197
0
10
Order By: Relevance
“…Operationalizing these constructs, Wolin and Bennett (1984) proposed that families organize their collective lives around a host of activities that foster family identity and fall into three categories: family celebrations, family traditions, and patterned family interactions. In a series of reports, Wolin, Bennett, and their colleagues described how family rituals might protect offspring from the harmful effects of parental alcoholism (Bennett, Wolin, & McAvity, 1988;Bennett, Wolin, Reiss, & Teitlebaum, 1987;Wolin & Bennett, 1984;Wolin, Bennett, Noonan, & Teitlebaum, 1980). Overall, they found that families whose rituals were subsumed by alcoholism were more likely to pass alcoholism on to the next generation and that offspring raised in alcoholic households fared less well when family routines were disrupted.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Operationalizing these constructs, Wolin and Bennett (1984) proposed that families organize their collective lives around a host of activities that foster family identity and fall into three categories: family celebrations, family traditions, and patterned family interactions. In a series of reports, Wolin, Bennett, and their colleagues described how family rituals might protect offspring from the harmful effects of parental alcoholism (Bennett, Wolin, & McAvity, 1988;Bennett, Wolin, Reiss, & Teitlebaum, 1987;Wolin & Bennett, 1984;Wolin, Bennett, Noonan, & Teitlebaum, 1980). Overall, they found that families whose rituals were subsumed by alcoholism were more likely to pass alcoholism on to the next generation and that offspring raised in alcoholic households fared less well when family routines were disrupted.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Os adolescentes referem que a bebida contribui para a ocorrência de brigas entre os membros, provocando um clima negativo no evento. Isso pode ser prejudicial aos adolescentes, uma vez que a família representa um modelo comportamental para os filhos (Wolin & Bennet, 1984). Tais acontecimentos podem minimizar a probabilidade do adolescente vir a desenvolver o senso de união.…”
Section: A Presença Deles é Importante () Me Sinto Importante Comunclassified
“…Il va sans dire que tous les membres de la famille doivent y trouver un profit, l'adolescent pouvant se voir investi d'un statut convoité, bénéficier de nouveaux privilèges ou de responsabilités accrues. Wolin et Bennett (1984) estiment que les rites familiaux constituent une fenêtre ouverte vers l'identité familiale. En définissant des façons précises de faire les choses et en délimi-tant le rôle de chacun, ils permettent à chaque membre d'avoir une représentation claire de ce qu'est sa famille.…”
Section: Le Rite De Passage Au Service De L'interventionunclassified